PENERAPAN PROSEDUR OPERASIONAL FLOATING DOCK 6000 TLC - Bambang Sudjasta (Bina Teknika, 2016)
Floating dock is one of the places for the repair of ship. It is a building that float on the sea, and has the ability to raise the vessel with longitudinal or transverse slope sizeable. It is needed a stable balance during the docking operation. In the implementation of docking the vessel must pay attention to the security elements of material and personnel. Should be avoided for slope occurring and ensuring the security and safety of the ship docking process. The implementation should always follow established procedures. the implementation should always follow established procedures.